A docência masculina na educação infantil em Manaus: representações de pais, mães e professores - Silva Júnior, João Raimundo dos Santos (2021)
Male teaching in early childhood education is a contemporary and controversial phenomenon, especially in our country, due to a group of factors: social, political, economical, cultural, and scientific. Such fact has caused tension and conflict among the members of the school communities, who have taken distinct positions, attitudes, and opinions regarding the consent of male teaching in early childhood, several times being discriminatory and prejudiced. This social reality motivated the development of this study, with the goal of comprehending the social representations of educational actors about being a male teacher in the early childhood segment in Manaus/Amazonas. Therefore, field research was conducted, based on qualitative epistemology, within the descriptive exploratory approach, with a questionnaire and situational group interview being applied to the early children’s fathers, mothers, and teachers who were enrolled at a City’s Childhood Educational Center (Centro Municipal de Educação Infantil - CMEI) of the public education system in Manaus. The answers obtained by the instruments were submitted to content analysis (FRANCO, 2012), and analyzed according to the methodologies proposed by The Theory of Social Representations (MOSCOVICI, 1978). The results indicated that most participants did not conceive male teaching in preschool in the capital of Amazonas. This opposing position of the group seems to be guided by their representations of being a teacher objectified in the image of a being who is inept, unpredictable, and unprepared for the educational service with children, being anchored in the clashes between male and female cisgenders, which innately qualified the woman and disqualified the man (PEREIRA, 2012); supported by the social roles of mother and father, with the maternal figure being considered the ideal profile for the teaching field, and the father having his competencies questioned or discredited by the interviewees; and supported by the suspicion of the possibility of pedophilia practices, enticement or child sexual abuse by the teacher, during hygiene practices, however exempting the female teacher from such illicit acts. Thus, the work glimpsed the possibility of producing materials that can serve as subsidies for future interventions in the educational field, in an attempt to minimize or remedy the difficulties faced by men in their teaching career in the children's segment. Furthermore, we recommend carrying out more research on the subject